Inhalasi Aromaterapi Lemon Menurunkan Frekuensi Mual Muntah pada Ibu Hamil - Siti Maesaroh; Mera Putri (Jurnal Kesehatan Metro Sai Wawai, 2019)
Background: The incidence of nausea, vomiting or emesis gravidarum in pregnant women reaches 50-90%, while hyperemesis gravidarum reaches 10-15% in Lampung Province. Purpose: prove the effect of lemon aromatherapy inhalation on nausea and vomiting in pregnant women in the first four months. Methods: This type of quantitative research with pre-experimental design was carried out in February - April 2018. The population in this study was the number of pregnant women in the first four months of pregnancy who experienced nausea and vomiting at UPT Karya Penggawa Public Health Center, Pesisir Barat District with a sample of 30 people. Accidental sampling sampling technique. The variables analyzed were the results of interventions in the administration of lemon aroma therapy inhalation. Data analysis using T test. Results: The study obtained the average frequency of nausea and vomiting before the intervention 17.37 times, whereas after the intervention dropped to 12.43 times. There is an inhalation effect of the aroma of lemon therapy on nausea and vomiting in pregnant women in the first four months of pregnancy (p value 0,000). Conclusion: Inhalation of lemon aroma therapy is effective in reducing the frequency of nausea and vomiting in pregnant women with a decrease of 4.86 times the frequency of nausea and vomiting. Inhalation of the aroma of lemon therapy becomes a part that can be applied as a complementary therapy to reduce the frequency of nausea, vomiting in care for pregnant women. Latar belakang: Angka kejadian mual muntah atau emesis gravidarum pada wanita hamil mencapai 50-90%, sedangkan hiperemesis gravidarum mencapai 10-15% di Provinsi Lampung. Tujuan: membuktikan pengaruh inhalasi aromaterapi lemon terhadap mual muntah pada ibu hamil trimester I. Metode: Jenis penelitian kuantitatif dengan rancangan pra experimental yang dilaksanakan pada pada bulan februari – april 2018. Populasi dalam penelitian ini adalah jumlah ibu hamil trimester I yang mengalami mual muntah di UPT Puskesmas Karya Penggawa Kabupaten Pesisir Barat dengan jumlah sampel 30 orang. Tehnik pengambilan sampel accidental sampling. Variabel yang dianalisis adalah adalah hasil intervensi pemberian inhalasi aroma terapi lemon. Analisis data menggunakan T test. Hasil: Penelitian memperoleh hasil rerata frekuensi mual muntah sebelum intervensi 17.37 kali, sedangkan setelah intervensi turun menjadi 12.43 kali. Ada pengaruh inhalasi aroma terapi lemon terhadap mual muntah pada ibu hamil trimester I (p value 0,000). Simpulan: pemberian inhalasi aroma terapi lemon efektif menurunkan frekuensi mual muntah pada ibu hamil dengan penurunan 4,86 kali frekuensi mual muntah. Inhalasi aroma terapi lemon menjadi bagian yang dapat diterapkan sebagai terapi komplementer untuk mengurangi frekeunsi mual muntah dalam asuhan pada ibu hamil.